2015
DOI: 10.1103/physrevb.92.174419
|View full text |Cite|
|
Sign up to set email alerts
|

Quantum tricriticality in antiferromagnetic Ising model with transverse field: A quantum Monte Carlo study

Abstract: Quantum tricriticality of a J1-J2 antiferromagnetic Ising model on a square lattice is studied using the mean-field (MF) theory, scaling theory, and the unbiased world-line quantum MonteCarlo (QMC) method based on the Feynman path integral formula. The critical exponents of the quantum tricritical point (QTCP) and the qualitative phase diagram are obtained from the MF analysis. By performing the unbiased QMC calculations, we provide the numerical evidence for the existence of the QTCP and numerically determine… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 49 publications
3
27
0
Order By: Relevance
“…It was shown that FOPT and continuous phase transition have been observed in a spin model with both nearest-neighbor and next-nearest neighbor interactions [71]. The effective theory for this model is just the Landau-Devonshire theory [71]. We can consider a similar model in graphene, whose elementary excitation is the Dirac fermion with N f = 2 and the spin freedom is naturally coupled to the Dirac fermion.…”
Section: Figmentioning
confidence: 99%
“…It was shown that FOPT and continuous phase transition have been observed in a spin model with both nearest-neighbor and next-nearest neighbor interactions [71]. The effective theory for this model is just the Landau-Devonshire theory [71]. We can consider a similar model in graphene, whose elementary excitation is the Dirac fermion with N f = 2 and the spin freedom is naturally coupled to the Dirac fermion.…”
Section: Figmentioning
confidence: 99%
“…From the theoretical point of view, the transverse Ising model on the square lattice is the simplest model to exhibit both classical and quantum phase transitions. For instance, when first-neighbor (J 1 ) antiferromagnetic (AF) interactions are considered, increasing a transverse magnetic field can change the ground-state of this model from a Néel AF long-range order to a polarized paramagnetic (PM) state at a quantum critical point [4]. By considering also second-neighbor antiferromagnetic interactions (J 2 ), the model becomes the so called J 1 -J 2 Ising model, in which frustration can be introduced by tuning g ≡ J 2 /J 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite several studies have addressed the magnetic behavior of the classical J 1 -J 2 Ising model, only few efforts have been made to understand the effect of transverse fields in this model [4,7,17]. Recently, a cluster operator approach was used to describe the highly frustrated limit (g = 0.5) of the quantum J 1 -J 2 Ising model at zero temperature [17].…”
Section: Introductionmentioning
confidence: 99%
“…We further study tricritical points of Heisenberg transitions in Dirac semimetals [19,21,[34][35][36][37] by extending the Ising fields to Heisenberg spins. The relevance of these universality classes to real materials like graphene or graphene-like systems will also be discussed.Lattice model and phase diagram.-It is known that the (2+1)-dimensional Ising model under both transversal and longitudinal Zeeman fields can realize a tricritical point at the phase boundary between first-and secondorder transitions [7]. The Hamiltonian on the honeycomb lattice is given bywhere σ denotes the Ising spins defined at each site, and and refer to nearest neighbors (NN) and nextnearest neighbors (NNN), respectively.…”
mentioning
confidence: 99%